Risk and prognosis of second corpus uteri cancer after radiation therapy for pelvic cancer: A population-based analysis - Yu, Guanhua; Wei, Ran; Li, Shuofeng; Wang, Yongjiao; Liu, Hengchang; Chen, Tianli; Guan, Xu; Wang, Xishan; Jiang, Zheng (Frontiers in Oncology, 2022)
Background Radiation therapy (RT) is a standard treatment for the local control of primary pelvic cancers (PPC), yet the risk of second corpus uteri cancer (SCUC) in PPC patients undergoing RT is still controversial. This study investigated the impact of RT on the risk of SCUC and assessed the survival outcome. Methods We queried nine cancer registries for PPC cases in the Surveillance, Epidemiology, and End Results (SEER) database. The cumulative incidence of SCUC was analyzed using Cox regression and Fine–Gray competing risk regression analysis. The Poisson regression analysis was employed to assess the standardized incidence ratios (SIRs) and radiation-attributed risk (RR) for SCUC. We evaluated the overall survival of patients with SCUC using the Kaplan–Meier method. Results Receiving radiotherapy was strongly associated with a higher risk of developing SCUC for PPC patients in Fine–Gray competing risk regression (No-RT vs. RT: adjusted HR = 1.77; 95% CI, 1.40–2.28; p < 0.001). The incidence of SCUC in PPC patients who received RT was higher than in the US general population (SIR, 1.66; 95% CI, 1.41–1.93; p < 0.05), but the incidence of SCUC in patients who did not receive RT was lower than with the US general population (SIR, 0.68; 95% CI, 0.61–0.75; p < 0.05). The dynamic SIR and RR for SCUC decreased with decreasing age at PPC diagnosis and decreased with time progress. In terms of overall survival, 10-year survival rates with SCUC after No-RT (NRT) and SCUC after RT were 45.9% and 25.9% (HR = 1.82; 95% CI, 1.46–2.29; p < 0.001), respectively. Conclusion Radiotherapy for primary pelvic cancers is associated with a higher risk of developing SCUC than patients unexposed to radiotherapy. We suggest that patients with pelvic RT, especially young patients, should receive long-term monitoring for the risk of developing SCUC.